Precomputing Shell Fragments for OLAP using Inverted Index Data Structure - Datta, D; Koley, A; Chatterjee, S (International Journal of Computer Sciences and Engineering, 2025)
Efficient methods to generate data cubes for On-Line Analytical Processing or OLAP are required for query processing and data analysis. OLAP involves multidimensional analysis of data and as well as selectively extracting and viewing data from different perspectives or points of view. In OLAP, a complex query can lead to many scans of the base relational database, leading to poor performance. This research paper provides an algorithm for the data cube generation suitable for OLAP systems in a fast way. The OLAP cube structure, based on aggregation operations and capable of fast retrieval of data, is extensively explored. The inverted index data structure, which is a mapping from content to index of the said content in any indexed data storage system, is used as an efficient tool for shell fragment computation. A study of efficiency and trade-offs involved in terms of processing complexity and storage space when compared to full cube computation are also provided here.